Electrocatalysis: Morphology and Structure Engineering in Nanofiber Reactor: Tubular Hierarchical Integrated Networks Composed of Dual Phase Octahedral CoMn2O4/Carbon Nanofibers for Water Oxidation (Small 26/2017). Issue 26 (July 2017) - Zhu, Han; Yu, Danni; Zhang, Songge; Chen, Jiawei; Wu, Wenbo; Wan, Meng; Wang, Lina; Zhang, Ming; Du, Mingliang
Abstract : In article number1700468, by Mingliang Du and co‐workers, a unique architecture of dual‐phase octahedral CoMn2 O4 /carbon hollow nanofibers is prepared via a two‐step heat‐treatment process including pre‐oxidation treatment and an Ostwald ripening process. Due to the intimate electrical and chemical coupling, these nanostructures exhibit excellent active oxygen evolution activity with overpotentials of 337 mV (10 mA cm −2 ) and Tafel slope of 82 mV dec −1 .